Pengembangan Game “Gemas Si Kakak Gara-Gara Asean” dalam Pembelajaran IPS Kelas VIII di SMP Negeri 2 Gedangsaridi Masa Pandemi - Sri Purwanti; Gunawan Sridiyakmiko (UM Purwokerto Press, 2022)
The COVID-19 pandemic has brought changes in various fields, including the field of education. Learning activities are carried out online, various facilities have been used, but the data shows that there is a decreasing interest and participation of students in participating in online learning, so it takes the creativity of teachers to innovate in order to create learning media that are in accordance with the characteristics of students, with the educational game